2018
DOI: 10.2134/jeq2017.12.0492
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine Transport through a Soil–Epikarst System

Abstract: Row crop and livestock production contaminate soils and groundwater of the karst aquifers within south‐central Kentucky's Pennyroyal Plateau. Transport of atrazine from field application to the epikarstic drainage system beneath a field with active row‐crop farming was investigated. The Crumps Cave study site is a shallow autogenic drainage system with a recharge area of ∼1 ha that contains two epikarst drains (WF‐1 and WF‐2) which were monitored for atrazine, deethylatrazine (DEA), and deisopropylatrazine (DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…() observed continuous flow and near immediate repsonses during storm events at an epikarst spring indentified as Waterfall One (WF1), suggesting the existence of a highly fractured and well‐developed epikarst conduit network. WF1 served as the sampling site for this study and is approximately 25 m from the suface and located 30 m from the cave's entrance, with an average drop of 4 m from the waterfall's appearance in the ceiling to floor of the cave (Vanderhoff, ; Groves et al ., ; Lerch et al ., ), where it disappears into the cave floor and joins the water table around 40 m below (Vanderhoff, ; Groves et al ., ). Multiple dye traces and hydrologic investigations conducted at WF1 place the estimated recharge area at around 1 ha and flow is perennial (Bandy et al ., ; Lerch et al, ).…”
Section: Study Sitesmentioning
confidence: 99%
“…() observed continuous flow and near immediate repsonses during storm events at an epikarst spring indentified as Waterfall One (WF1), suggesting the existence of a highly fractured and well‐developed epikarst conduit network. WF1 served as the sampling site for this study and is approximately 25 m from the suface and located 30 m from the cave's entrance, with an average drop of 4 m from the waterfall's appearance in the ceiling to floor of the cave (Vanderhoff, ; Groves et al ., ; Lerch et al ., ), where it disappears into the cave floor and joins the water table around 40 m below (Vanderhoff, ; Groves et al ., ). Multiple dye traces and hydrologic investigations conducted at WF1 place the estimated recharge area at around 1 ha and flow is perennial (Bandy et al ., ; Lerch et al, ).…”
Section: Study Sitesmentioning
confidence: 99%
“…Among the 20 European Union (EU) member states for which complete data are available, Italy is the third EU state for the sale of pesticides in 2016 with nearly 60 million kg sold each year (EUROSTAT, 2018). Indeed, recent studies reported the presence of ATR and its DPs in water of Italy (Ghirardelli et al, 2020;Hakoun et al, 2017;Lerch et al, 2018;Sassine et al, 2017;Vonberg et al, 2014a). In the Campania region, southern Italy, thanks to the high fertility of the territory due to the large presence of volcanic soils distributed throughout the region, agricultural activity is highly developed since ancient Roman times.…”
Section: Introductionmentioning
confidence: 98%
“…To understand these processes, a wide variety of techniques are implemented. Researchers utilized geophysical methods [4], geochemical isotopic tracer methods [5], hydrograph analyses [6], and a combination of these approaches [7]. Recent advances in lidar and photogrammetry techniques produce high resolution models of subsurface conduits that allow for the interactive analysis of cave features after data collection [8][9][10].…”
Section: Introductionmentioning
confidence: 99%